Are the Asia and Pacific Small States Different from Other Small States? - Tumbarello, Patrizia (IMF Working Papers; Working Paper, 2013)
The small states of the Asia and Pacific region face unique challenges in raising their growth potential and living standards relative to other small states due to their small populations, geographical isolation and dispersion, narrow export and production bases, exposure to shocks, and heavy reliance on aid. Higher fixed government costs, low access to credit by the private sector, and capacity constraints are also key challenges. The econometric analysis confirms that the Pacific Island Countries (PICs) have underperformed relative to their peers over the last 20 years. Although these countries often face more limited policy tools, policies do matter and can further help build resilience and raise potential growth, as evidenced in the recent business cycle. The Asia and Pacific small states should continue rebuilding buffers and improve the composition of public spending in order to foster inclusive growth. Regional solutions should also continue to be pursued.